The differential effects of azithromycin on the airway epithelium in vitro and in vivo - Slater, Mariel; Torr, Elizabeth; Harrison, Timothy W.; Forrester, Doug L.; Knox, Alan; Shaw, Dominick E.; Sayers, Ian (Wiley, 2016)
Macrolides including azithromycin (AZM) can improve clinical symptoms in asthma regardless of infection status. The mechanisms underlying these benefi- cial effects are yet to be elucidated. The aim of this study was to determine the effect of AZM on the airway epithelial barrier both in an in vitro model and in patients with asthma. Primary human bronchial epithelial cells (HBEC) were grown at air liquid interface (ALI) and challenged using lipopolysaccharides from Pseudomonas aeruginosa. AZM was added at various stages and barrier integrity assessed using transepithelial electrical resistance (TEER) and permeability to FITC-dextran. MMP-9 levels were measured using ELISA. AZM enhanced barrier integrity (TEER/FITC-dextran), increased thickness, suppressed mucin production, and MMP-9 release during the formation of a normal epithelial barrier in vitro. MMP-9 levels inversely correlated with TEER. AZM also enhanced maintenance of the barrier and facilitated repair post-LPS challenge. To provide translation of our findings, 10 patients with moderatesevere asthma were recruited and received 250 mg AZM o.d for 6 weeks. Bronchial biopsies taken pre- and post-AZM treatment did not show evidence of increased epithelial barrier thickness or decreased mucin production. Similarly, bronchial wash samples did not show reduced MMP-9 levels. Overall, our data show that AZM can significantly improve the development of a normal bronchial epithelial barrier in vitro, mimicking reepithelization postinjury. AZM also suppressed MMP-9 release which correlated with barrier integrity, suggesting a putative mechanism. However, these effects were not observed in biopsy samples from asthma patients treated with AZM, possibly due to small sample size.